The balance In the six dimensions of space-time description of quantum mechanics phenomena and nature of time - Mousavi, Seyed Kazem (Universitas Sebelas Maret, 2023)
This study presents a theory with a six-dimensional space-time structure, R^6, in order to describe quantum mechanic phenomena, the time arrow and quantum gravity. The interpretation of quantum world phenomena using four-dimensional space-time would be a very complicated and indescribable task. The dual wave-particle behavior, entanglement, quantum corridors, etc., represent the complex space-time structure. Previous studies indicate that complicated behaviors of particles in quantum mechanics are basically considered as the inherent behavior of those particles. The theoretical framework of the balance is the transformation of imaginary dimensions into geometric dimensions and the description of quantum mechanical phenomena using external Euclidean geometry. The six-dimensional space-time structure consists of three space and three time dimensions and the time arrow is the result of the impossibility of the existence of matter in six space-time dimensions, and the direction of the arrow is aligned with the expansion of the universe.